A coefficient inequality for the class of analytic functions in the unit disc. (22nd October 2003) - Polatoğlu, Yaşar; Bolcal, Metın
Abstract : The aim of this paper is to give a coefficient inequality for the class of analytic functions in the unit discD = { z | | z |   < 1 } .